Studi Kualitatif Keluarga sebagai Potensi dalam Upaya Kesiapsiagaan Bencana pada Lansia - Mahathir Mahathir; Putri Dwi Rusmayanti; Fitra Yeni (JURNAL KESEHATAN MERCUSUAR, 2022)
Family is the minor structure that is essential in preparing for disaster preparedness. Older adults are recognized as a vulnerable group to get an enormous impact from a disaster occurrence. Family is a potential resource that must be utilized in preparing older adults to reduce the risk of catastrophic impacts of a disaster occurrence. This study aimed to review the perception of the families in recognizing their potential to prepare older adults for disaster. This study used descriptive qualitative research methods. This study has conducted semi-structured interviews of five family members belonging to older adults. Data analysis in this study used the Stevick Collaizy Keen analysis method. The results of this study found five essential themes that represent the perception of families in helping older adults deal with disasters. The themes were earthquakes, tsunamis and tidal floods as potential hazards, older adults' disaster preparedness bags containing valuable documents and other items, home environment arrangements for elderly preparedness, older adults self-rescue indoors during a disaster and older adults self-rescue outdoors during a disaster. Families must pay specific attention in order to increase awareness and preparedness to help older adults in dealing with disasters.